Genetic diversity studies in pepper (Capsicum spp) - Agyare, Richard Yaw (2014)
A thesis submitted to the Department of Crop and Soil Sciences, Faculty of Agriculture, KNUST, Kumasi in partial fulfillment of the requirements for the degree of Master of Science, 2013